2020
DOI: 10.1002/adem.202000913
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Robust Superhydrophobic Ni Coating with Micro–Nano Dual‐Scale Structures on 316L Stainless Steel

Abstract: Herein, a superhydrophobic Ni coating is prepared on 316L stainless steel by electrodeposition and low energy modification with tetradecanoic acid. After 20 min of electrodeposition with a current density of 8 A dm−2, a Ni coating with micro–nano dual‐scale structures is obtained. The coating becomes superhydrophobic with a water contact angle (WCA) of 160.4° and a sliding angle (SA) of 8.3° after being immersed in the tetradecanoic acid solution (5 g L−1, 12 h). A two‐level structure model is established for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…There are highly abundant superhydrophobic surfaces with water contact angles (WCAs) larger than 150° and water sliding angles (WSAs) smaller than 10° in nature, such as lotus leaves, rice leaves, and butterfly wings, which provide rich sources of inspiration for the development of novel functional materials. Inspired by animals and plants in nature, plenty of artificial superhydrophobic surfaces have been prepared through various methods such as sol–gel, , chemical etching, , electrodeposition, , anode oxidation, , and laser ablation. Moreover, the potential applications of the superhydrophobic surfaces, including self-cleaning, ,, antifogging, , antibiofouling, , anticorrosion, , oil/water separation, and anti-icing, , have been extensively explored. However, the water-repellency property of most of the reported superhydrophobic surfaces is easily degraded under external force, oil pollution, a corrosion medium, or a cold environment because of damage of the micro/nanostructures or the decomposition of the low-surface-energy molecules, which limits the practical application of the superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are highly abundant superhydrophobic surfaces with water contact angles (WCAs) larger than 150° and water sliding angles (WSAs) smaller than 10° in nature, such as lotus leaves, rice leaves, and butterfly wings, which provide rich sources of inspiration for the development of novel functional materials. Inspired by animals and plants in nature, plenty of artificial superhydrophobic surfaces have been prepared through various methods such as sol–gel, , chemical etching, , electrodeposition, , anode oxidation, , and laser ablation. Moreover, the potential applications of the superhydrophobic surfaces, including self-cleaning, ,, antifogging, , antibiofouling, , anticorrosion, , oil/water separation, and anti-icing, , have been extensively explored. However, the water-repellency property of most of the reported superhydrophobic surfaces is easily degraded under external force, oil pollution, a corrosion medium, or a cold environment because of damage of the micro/nanostructures or the decomposition of the low-surface-energy molecules, which limits the practical application of the superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…There are highly abundant superhydrophobic surfaces with water contact angles (WCAs) larger than 150°and water sliding angles (WSAs) smaller than 10°in nature, such as lotus leaves, rice leaves, and butterfly wings, which provide rich sources of inspiration for the development of novel functional materials. Inspired by animals and plants in nature, plenty of artificial superhydrophobic surfaces have been prepared through various methods such as sol−gel, 1,2 chemical etching, 3,4 electrodeposition, 5,6 anode oxidation, 7,8 and laser ablation. 9−13 Moreover, the potential applications of the superhydrophobic surfaces, including self-cleaning, 3,4,14−17 antifogging, 18,19 antibiofouling, 20,21 anticorrosion, 5,6 oil/water separation, 22−24 and anti-icing, 20,25−27 have been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Subsequently, hydrophobicity can be improved by modification with low surface energy substances. 38,39 Hydrogen is inevitably generated during electrodeposition. A hierarchical structure can be obtained by H 2 bubbletemplated electrodeposition.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Subsequently, hydrophobicity can be improved by modification with low surface energy substances. 38,39…”
Section: Introductionmentioning
confidence: 99%
“…The electroplating process has many advantages, such as a simple preparation method, low cost, controllable plating conditions, and unlimited base size [23][24][25]. It was found that plating accelerated the dopamine polymerization rate and facilitated the preparation of PDA coating [26][27][28].…”
Section: Introductionmentioning
confidence: 99%